A Critique of the Caps on Deficits and Debt in the European Monetary Union - Jan Priewe (Wirtschaftsdienst)
Abstract The reference values for public deficits and debt came into the Maastricht Treaty more or less by coincidence. Later attempts to justify them in terms of economic theory failed. The values narrow fiscal space for member states with high debt and tend to create debt levels that are too low in the others, thereby polarising the 19 member states in two groups. Fiscal policy can hardly support monetary policy, which is stuck at the zero lower bound. This serves as an inherent contractionary bias for fiscal policy in the European Monetary Union. To confront the prospect of lower interest than growth rates, the caps should be discarded.